[OP.7C.07] REFERENCE VALUES FOR AORTIC PULSE WAVE VELOCITY IN PORTUGUESE CHILDREN AND ADOLESCENTS - THE PORTUGUESE VASCULAR PHENOTYPE IN CHILDREN AND ADOLESCENTS (PORT-VASPH) COHORT. (September 2017) - Pereira, T.; Maldonado, J.; Martins, J.; Carvalho, M.
Abstract : Objective: Carotid-femoral pulse wave velocity (PWV) is the gold-standard method to estimate aortic stiffness, and has been clearly associated with cardiovascular risk in different clinical subsets. Still, its use in clinical practice is still limited in some specific groups, particularly in pediatrics, due to the absence of reference values for this population. This subanalysis of the PORT-VASPh Cohort aimed to propose preliminary reference values in Portuguese children and adolescents, based on a statistical definition that considers the fundamental physiological role of aging in arterial stiffness. Design and method: The PORT-VASPh cohort has 402 children and adolescents enrolled so far, age ranging from 5 to 17 years. The overall health profile for each participant was defined based on three clinical evaluations, in which blood pressure (BP) was measured under standard conditions over the brachial artery with a clinically validated automatic sphygmomanometer (OMRON 705IT) and an appropriately sized cuff. Gender-specific percentiles were used for the definition of the individual BP phenotype. For the proposal of reference values for PWV, data were collected from 295 healthy and normotensive participants included in the cohort, 59.3% males and 40.7% females, with a mean age of 11.84 ± 2.86 years (ranging from 5 to 17 years) and a body mass index (BMI) of 18.75 ± 3.07 kg/m 2 . Carotid-femoral PWV was measured to all participants with the Complior SP device, complying with the methodological recommendations. All participants were evaluated by the same clinician. Results: Gender-specific percentile tables, accounting for age, were obtained, as depicted in Figure 1. Mean PWV was 6.14 ± 0.99 m/s, and was higher in boys as compared with girls (6.29 ± 1.00 m/s versus 5.92 ± 0.93 m/s, respectively; p = 0.002). A significant correlation of PWV with age, BMI, systolic and diastolic BP and family history of hypertension was identified Figure 1. Gender-specific percentiles for carotid-femoral pulse wave velocity. Figure. No caption available. Conclusions: The availability of reference tables for PWV in children and adolescents is necessary, as it would allow the incorporation of the arterial stiffness concept into pediatric clinical decision, thus contributing for a better definition of the adequate preventive strategies for these particular populations.